Recovery From Repeat Mild Traumatic Brain Injury in Adolescent Rats Is Dependent on Pre-injury Activity State - Ferguson, Lindsay; Giza, Christopher C.; Serpa, Rebecka O.; Greco, Tiffany; Folkerts, Michael; Prins, Mayumi L. (Frontiers in Neurology, 2021)
Adolescents and young adults have the highest incidence of mild traumatic brain injury (mTBI); sport-related activities are a major contributor. Roughly a third of these patients diagnosed with mTBI are estimated to have received a subsequent repeat mTBI (rTBI). Previously, animal studies have only modeled mTBI in sedentary animals. This study utilizes physical activity as a dependent variable prior to rTBI in adolescent rats by allowing voluntary exercise in males, establishing the rat athlete (rathlete). Rats were given access to locked or functional running wheels for 10d prior to sham or rTBI injury. Following rTBI, rathletes were allowed voluntary access to running wheels beginning on different days post-injury: no run (rTBI+no run), immediate run (rTBI+Immed), or 3 day delay (rTBI+3dd). Rats were tested for motor and cognitive-behavioral (anxiety, social, memory) and mechanosensory (allodynia) dysfunction using a novel rat standardized concussion assessment tool on post-injury days 1,3,5,7, and 10. Protein expression of brain derived neurotrophic factor (BDNF) and proliferator-activated gamma coactivator 1-alpha (PGC1α) was measured in the parietal cortex, hippocampus, and gastrocnemius muscle. Sedentary shams displayed lower anxiety-like behaviors compared to rathlete shams on all testing days. BDNF and PGC1α levels increased in the parietal cortex and hippocampus with voluntary exercise. In rTBI rathletes, the rTBI+Immed group showed impaired social behavior, memory impairment in novel object recognition, and increased immobility compared to rathlete shams. All rats showed greater neuropathic mechanosensory sensitivity than previously published uninjured adults, with rTBI+3dd showing greatest sensitivity. These results demonstrate that voluntary exercise changes baseline functioning of the brain, and that among rTBI rathletes, delayed return to activity improved cognitive recovery.